Ecological Footprints and Appropriated Carrying Capacity: What Urban Economics Leaves Out. (May 2017) - Rees, William E.
This article uses the concepts of human carrying capacity and natural capital to develop a framework to evaluate a city's 'ecological footprint'. It argues that prevailing economic assumptions regarding urbanisation and the sustainability of cities must be revised in light of global ecological change.